Archaeology of large-scale manipulation of prey, The: the economic and social dynamics of mass hunting - Carlson, Kristen; Bement, Leland C. (Colorado State University. Libraries, 2018)
Includes bibliographical references and index. Expands the understanding of large-scale hunting methods beyond the customary role of subsistence and survival to include the social and political realms where large-scale hunting adaptations evolved, primarily from the Americas and spanning from the Folsom Period on the Great Plains to the ethnographic present in Australia.--Provided by publisher. An introduction to large scale manipulation of prey: an economic and social discussion / Leland C. Bement -- Territory formation among ancestral Blackfoot bison hunters of the Northwestern Plains / María Nieves Zedeño -- Communal hunting by Aboriginal Australians: archaeological and ethnographic evidence / Jane Balme -- Driving the caribou: Greenlandic hunting drive systems and ethical aspects / Ulla Odgaard -- Are models of ancient bison population structure valid? / David Maxwell and Jonathan Driver -- Micro-analytical evidence of Folsom-aged communal hunting on the U.S. Southern Great Plains / Adam C. Graves -- The development of Paleoindian large scale bison kills: an isotopic comparison / Kristen Carlson and Leland Bement -- A new look at old assumptions: Paleoindian communal bison hunting, mobility, and stone tool technology / John D. Speth.